Bibliometrics and Academe - Martínez, Luis-Javier (Anuario ThinkEPI, 2009)
Recent criticisms and controversies about abuse or misuse of bibliometric research evaluation are placed in the context of general conflicts of values that knowledge industrialization is bringing about, as bibliometrics seems to be a tool of post-academic or industrial science, a form of scientific work that breaks away from traditional academic principles.